Sensitivity patterns of Bordetella bronchiseptica strains, isolated from swine, to antimicrobial agents - Brito, Maria Aparecida V.P.; Brito, José Renaldi F.; Peffer, Itamar A. (Pesquisa Agropecuaria Brasileira, 2014)
The sensitivity patterns of Bordetella bronchiseptica strains isolated from swine nasal cavities (59 strains in 1977, 32 in 1978, 165 in 1979, 41 in 1980, and 24 in 1981) to fourteen antimicrobial agents were determined. Eighty to 100 percent of the isolated strains were sensible to chloramphenicol, colistin, gentamicin, kanamycin, neomycin and tetracycline. In addition, above 80 percent of these strains were resistant to ampicillin, streptomycin, lincomycin and penicillin. In both cases, the percentages of sensible or resistant strains did not change significantly among the observed years. Variable results were obtained with cephalothin and erythromycin. Thus, a trend for an annual increasing of sensitivity among the isolates was observed with these drugs. In contrast there were an annual decreasing in sensitivity among the isolates to sulfadiazine and trimethoprim-sulfamethoxazole. This fact ocurred with the increasing utilization of these drugs in the swine atrophic rhinitis control.